KOMPOSISI INDUSTRI YANG MEMBANGUN SEKTOR PERTANIAN SULAWESI TENGAH - Marwan R. Yantu; Sisfahyuni Sisfahyuni; Ludin Ludin; Taufik Taufik (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
The aim of the study was to analyze the composition (mix) industries that have been supported the agriculture sector in Sulawesi Tengah economy. Method of analyses used was Shift and Share analysis. Data used were time series data, such as Gross Domestic Regional Product of Central Sulawesi, and Gross Domestic Product of Indonesia, 2000 – 2007.  The analyses results showed that the agricultures with its subsectors have negative values of the mix industries. The ranking of the mix (subsectors) industries from the best until the worse are : (i) perkebunan; (ii) perikanan; (iii) tanaman bahan makanan; (iv) peternakan; and (v) kehutanan